ANALISIS JABATAN KETUA BADAN EKSEKUTIF MAHASISWA FAKULTAS EKONOMI DAN SOSIAL UNIVERSITAS JENDERAL ACHAMAD YANI YOGYAKARTA - Nurhalizah, Lutfia Fifi; Dian Juliarti Bantam; Sanca Cintia Jehadu; Noviana Puspita Sari (Lumbung Pare Cendekia, 2024)
Organization is a place where people work together effectively and efficiently to achieve common goals that have been set, with job analysis can determine the duties, responsibilities, authority and also the relationship between one another. The purpose of this research is about job descriptions, job specifications and job evaluations at the Head of the BEM Organization. This research uses a qualitative approach with data collection techniques conducted by interview with phenomenological research design and thematic analysis. The sample used was 3 people who had positions as chairman, vice chairman and members. The results of this study are a job analysis that raises job descriptions, job specifications and job evaluations. The job description of the BEM Chairperson is to coordinate members, be the person in charge of the activities of each event, ensure that each work program prepared is appropriate and effective, the job specification is skills in public speaking and problem solving. Job evaluation is carried out by the chairman every 2 months for all members or after the activity takes place. In addition, job evaluation is also carried out to departments that are directly related to the chairman. The conclusion of this research is that the job analysis of the Head of BEM produces a job description, namely coordinating members, responsibility for activities/events, and ensuring the effectiveness of work programs.